Tegument changes of Schistosoma japonicum and Schistosoma mansoni in mice treated with artemether - Xiao Shu-Hua; Shen Bing-Gui; Horner Jack; Catto Brian A. (Acta Pharmacologica Sinica; Vol 17, No 6 (November 1996): Acta Pharmacologica Sinica, 2016)
AIM: To study the effect of artemether (Art) on the tegument of schistosomes. METHODS: Mice infected with S japonicum cercariae for 7 and 35 d, or with S mansoni cercariae for 49 d were treated intragastrically with Art 200-300 mg.kg-1.d-1 for 2 d. Schistosomes were collected in groups of 2 mice at various intervals after medication for scanning electron microscopic observation. RESULTS: The tegumental changes induced by Art appeared to be similar in S japonicum and S mansoni: swelling and fusion of tegumental surfaces, vesicle formation and collapse of discoid-like sensory structures. In S japonicum the emergence of tegumental alterations was earlier in 7-d-old schistosomulae than that in 35-d-old adult worms. CONCLUSION: Art injured the teguments of S japonicum and S mansoni.